2013
DOI: 10.1002/hep.26072
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fat loss in advanced nonalcoholic steatohepatitis: Are alterations in serum adiponectin the cause?

Abstract: Advanced liver fibrosis in nonalcoholic steatohepatitis (NASH) is often accompanied by a reduction in hepatic fat to the point of complete fat loss (burnt-out NASH), but the mechanisms behind this phenomenon have not been elucidated. Adiponectin is raised in cirrhosis of any cause and has potent antisteatotic activity. In this study we examined 65 patients with advanced biopsy-proven NASH (fibrosis stage 3-4) and 54 with mild disease (fibrosis stage 0-1) to determine if disappearance of steatosis correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
75
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 41 publications
13
75
0
1
Order By: Relevance
“…Recent studies demonstrated converting FFA to TG is critical in protecting the liver from FFA-induced lipotoxicity. Clinical observations reveal patients with advanced steatohepatitis express significantly reduced key hepatic lipogenic enzymes, and have increased hepatic FFA and significantly reduced hepatic TG (Nagaya et al, 2010, van der Poorten et al, 2013). Specifically, genetic interruption of hepatic TG synthesis leads to increased hepatic FFA accumulation, inflammation, fibrosis, and exacerbated liver damage (Yamaguchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated converting FFA to TG is critical in protecting the liver from FFA-induced lipotoxicity. Clinical observations reveal patients with advanced steatohepatitis express significantly reduced key hepatic lipogenic enzymes, and have increased hepatic FFA and significantly reduced hepatic TG (Nagaya et al, 2010, van der Poorten et al, 2013). Specifically, genetic interruption of hepatic TG synthesis leads to increased hepatic FFA accumulation, inflammation, fibrosis, and exacerbated liver damage (Yamaguchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Visceral adipose tissue is also an independent risk factor for hepatic necro-inflammation and fibrosis. 141 Ethnicity modulates obesity as a risk factor for NAFLD.…”
Section: Visceral Obesitymentioning
confidence: 99%
“…However, only the intermediate NFS and APRI scores between published low and high cut-offs correlated directly with the presence of steatosis by ultrasonography. The lack of significant association between the NFS or APRI scores higher than published high cut-off values and hepatic steatosis could be due to "burn-out" NASH as advanced liver fibrosis in NASH is often accompanied by a reduction in hepatic fat to the point of complete fat loss [17] . Alternatively, the lack of association might be attributed to type Ⅱ error due to the small number of participants who had high NFS or APRI scores.…”
Section: Discussionmentioning
confidence: 86%